Attraction of the cutaneous leishmaniasis vector Nyssomyia neivai (Diptera: Psychodidae) to host odour components in a wind tunnel - Pinto, Mara Cristina [UNESP]; Bray, Daniel P.; Eiras, Alvaro E.; Carvalheira, Henrique P. [UNESP]; Puertas, Camila P. [UNESP] (Biomed Central Ltd., 2012)
Background: Laboratory studies of host-seeking olfactory behaviour in sandflies have largely been restricted to the American visceral leishmaniasis vector Lutzomyia longipalpis. In comparison, almost nothing is known about the chemical ecology of related species, which transmit American cutaneous leishmaniasis (ACL), due in part to difficulties in raising these insects in the laboratory. Understanding how ACL vectors locate their hosts will be essential to developing new vector control strategies to combat this debilitating disease.Methods: This study examined host-odour seeking behaviour of the ACL vector Nyssomyia neivai (Pinto) (=Lutzomyia neivai) using a wind tunnel olfactometer. The primary aim was to determine whether field-collected female N. neivai would respond to host odours in the laboratory, thereby eliminating the need to maintain colonies of these insects for behavioural experiments. Responses to two key host odour components, 1-octen-3-ol and lactic acid, and a commercially-available mosquito lure (BG-Lure (TM)) were assessed and compared relative to an air control. We also tested whether trials could be conducted outside of the normal evening activity period of N. neivai without impacting on fly behaviour, and whether the same flies could be used to assess baseline responses to air without affecting responses to octenol, thereby reducing the number of flies required for experiments.Results: Octenol was found to both activate host-seeking behaviour and attract female N. neivai in the wind tunnel, while lactic acid elicited weaker responses of activation and attractiveness under identical conditions. The BG-Lure did not activate or attract N. neivai under test conditions. Further experiments showed that sandfly behaviour in the wind tunnel was not affected by time of day, such that experiments need not be restricted to nocturnal hours. Moreover, using the same flies to measure both baseline responses to air and attraction to test compounds did not affect odour-seeking behaviour.Conclusions: The results of this study demonstrate that N. neivai taken from the field are suitable for use in laboratory olfactometer experiments. It is hoped this work will facilitate further research into chemical ecology of this species, and other ACL vectors.
Keywords: Kairomone; Octenol; Lactic acid; Ammonia; Caproic acid; BG Lure; Sandflies; Vector control; Wind tunnel